The theoretical framework for the relationship of metacognitive awareness, time perspective and academic procrastination - Roslan, Samsilah; Mad Baguri, Ezza (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
This is a conceptual paper that discusses the relationship between metacognitive awareness, time perspective and academic procrastination based on theoretical framework. Academic procrastination creates problems such as stress for students, reduces accuracy that will affect academic track in accomplishing writing tasks and threatens quality of research work among master’s students. As such, it should be investigated as a serious disadvantage in the educational context. Underlying the main theory of Social Cognitive theory by Bandura, cognitive process in personal and environmental factors determine individual behaviour. Self-regulation, being the by-product of cognitive process, is the key to reducing academic procrastination. Acquiring a high degree of self-regulation from metacognitive awareness, which enables self-monitoring and self-evaluating, will discourage individuals from yielding to negative behaviour. Additionally, the process of forethought and goal setting also involve the element of time perspective. Individuals with future time perspective have futuristic goals and are motivationally-driven for pleasure reward whereas individuals with present time perspective will underestimate time and discount future reward. In conclusion, it can be established that high metacognitive awareness and future time perspective could help overcome academic procrastination apart from other theories such as Temporal Motivation Theory (TMT) and Islamic perspectives.